Bronchiectasis Exacerbation Increases the Risk of Adverse Renal Outcomes—Results From a Large Territory‐Wide Cohort Study - Wang Chun Kwok; Chung Ki Tsui; Leung Sze Him Isaac; Chun Ka Emmanuel Wong; Terence Chi Chun Tam; James Chung Man Ho; Desmond Yat Hin Yap (The Clinical Respiratory Journal)
ABSTRACT Introduction Bronchiectasis exacerbation (BE) is associated with unfavorable sequelae in other organs such as the cardiovascular system; data regarding its impact on adverse term renal outcomes, however, is lacking. Methods A territory‐wide retrospective cohort study was conducted in Hong Kong between 1/1/1993 and 31/12/2017. All patients with bronchiectasis followed in the public healthcare system in 2017 were classified as “Exacerbators” or “Non‐Exacerbators,” and their adverse renal outcomes (renal progression [decrease in eGFR by 30 mL/min lasted for more than 12 months during follow up], acute kidney injury [AKI], and annual rate of eGFR decline) in the ensuing 7 years were compared. Results were also analyzed in the 1:1 propensity score matched (PSM) cohort. Results A total of 7929 patients (1074 “Exacerbators” group and 6855 “Non‐exacerbators”) were followed for 6.2 ± 1.6 years. A total of 1570 patients (19.8%) had renal progression, and 935 (11.8%) patients developed AKI. “Exacerbators” showed significantly increased risk of renal progression (adjusted odds ratio [aOR] 1. 27 [95% CI 1.08–1.50, p = 0.003]), more rapid eGFR decline (−3.67 [−1.74 to −6.54] vs. −3.03 [−1.56 to −5.12] mL/min/1.73 m2/year, p = 0.004) and AKI (aOR 1.99; 95% CI 1.44–2.73, p < 0.001) than the “Non‐exacerbators.” Annual number of BE was associated with renal progression (aOR 1.45; 95% CI 1.22–1.72, p < 0.001) and AKI (aOR 2.00; 95% CI 1.38–2.91, p < 0.001). Results were consistent in the analysis with the PSM cohort. Conclusions Renal progression and AKI are common among patients with bronchiectasis, and BE is an independent risk factor for adverse renal outcomes.